058 ANTI-CASPR2-ANTIBODY associated encephalitis in a 63-year old male with chronic lymphocytic leukaemia. Issue 6 (24th May 2018) - Lilley, Kate; Swayne, Andrew; Watson, Emily; Kee, Rachel; Wong, David; Lehn, Alexander; Brown, Helen; O'Gorman, Cullen; Sheikh, Nabeel; Bird, Robert; Prain, Kerri; Gillis, David; et al.
Abstract : Introduction: This case from a tertiary neurology centre reports a novel association between the emerging clinical entity of anti-contactin associated protein-2 (CASPR-2) antibody encephalitis and chronic lymphocytic leukaemia (CLL). Case: We describe a 63 year old Maori male truck-driver who presented with progressive altered personality, speech, cognition and perception over 9 months. The patient also developed choreiform movements, broad-based gait, incontinence, sleep apnoea with type 2 respiratory failure and episodic loss of consciousness. 12 months prior, he had been diagnosed with low-risk CLL, for which he remained untreated. MRI of the brain revealed mid-sagittal bilateral mid-temporal T2/FLAIR hyperintensities. Cerebrospinal fluid examination showed a mononuclear pleocytosis (WCC 270×10^6/L) with 15% of these CD5/CD19/CD23 positive and 92% CD3/CD5 positive CD 19 negative on flow cytometry, protein was also elevated at 2600 mg/L. The interplay between CLL and inflammation is uncertain. Anti-Caspr2-antibody was identified in CSF and serum. The patient was treated with a combination of fludarabine, cyclophosphamide, rituximab, dexamethasone and intravenous immunoglobulin (IVIG). Clinical status improved and antibody titre decreased from 580 to 241 pM in three weeks and to 55pM (negative <85 pM) at five months. Symptoms worsened when IVIG doses were missed. He returned home after inpatient rehabilitation, showed striking clinical improvement at 12 month follow-up and continues on maintenance IVIG therapy. Conclusion: Whilst paraneoplastic VGKC encephalitis has been described associated with a number of malignancies, this is the first reported case of CASPR-2 antibody present in association with CLL. References: . Van Sonderen A, Petit-Pedrol M, Dalmau J, Titulaer MJ. The value of LGI1, Caspr2 and voltage-gated potassium channel antibodies in encephalitis. Nature Reviews Neurology2017;13(5):290–301. . Nogai H, Israel-Willner H, Zschenderlein R, Pezzutto A. Improvement in Paraneoplastic Limbic Encephalitis after Systemic Treatment with Rituximab in a Patient with B-Cell Chronic Lymphocytic Leukaemia. Case Reports in Haematology2013;2013:Article ID958704. . Van Sonderen A, Ariño H, Petit-Pedrol M, et al. The Clinical Spectrum of Caspr2 antibody-associated disease. Neurology2016;87:521–528. . Gultekin SH, Rosenfeld MR, Voltz R, Eichen J, et al. Paraneoplastic limbic encephalitis: Neurological symptoms, immunological findings and tumour association in 50 patients. Brain2000;123:1481–1494.